Exploring the design framework for food waste recycling awareness in Chow Kit Wet Market. - Hui, Lee Chia; Shari, Zalina; Zairul, Mohd; D’Silva, Jeffrey Lawrence (Human Resources Management Academic Research Society (HRMARS), 2024)
In Malaysia, the overall waste composition is dominated by food waste (FW) due to excessively convenient food accessibility, urbanisation and progressive prosperity. Due to mismanagement, FW problems are significant in most wet markets in Kuala Lumpur. Despite the significant waste stream and availability of FW recycling centres in urban areas, there is a relatively low rate of recycling organic waste compared with other major waste categories. Therefore, this research aims to explore the design framework for integrated recycling in the existing wet market to improve public outreach of FW recycling. Chow Kit Market was explored from a human-centric perspective to analyse the existing FW management and through observation of market workflow and spatial design. This research aims to investigate the challenges of current FW recycling practices in an existing wet market and propose appropriate design strategies to optimise FW recycling for improved public outreach. It supports the government’s commitment to achieving Sustainable Development Goal (SDG) 12 of responsible consumption and production and SDG 8 by promoting sustained economic growth through improved resource efficiency and a new circular economy. This paper raises awareness for improving the implementation of FW recycling strategies in urban wet markets. It is hoped that the sustainability of the FW system for innovative recycling strategies provided in this paper can be further explored in other food retail operations in Malaysia.